Safety peace in the Holy Quran - Majdoubah, Samira Ahmed Mostafa; Othman, Fadlan bin Mohammed; Bin Sakt, Ahmed Asmadi; Bogue, Tinko Intan Zerena Bint Tanko (Journal of Humanities & Social Sciences, 2017)
Praise be to God who blessed the Muslims of security in the world and the afterlife and prayers and peace upon our Prophet Mohammad (p.b.u.h). Security and peace are of the great blessings that God bestowed on the Islamic nation individuals and groups. They are playing a very important role in the achievement and innovation. They are essential need for the continuation of life and the habitation of land, and without it doesn’t have the stability and happiness, and this is done only by referring to the teaching of Koran and the Sunnah which guide man to the right proper way, and are making him happy and flood it safety and security upon him, and give psychological serenity and heart satisfaction feeling of comfortably to overcome the difficulties of life and its problems. This study was based on inductive analytical subject of (peaceful security in the Quran), the researcher states through the study the definition of peace and security in the language and in the terminology of peace, words and their meanings as set out in the context of the Qur'an with an indication to the importance of achieving the security of peace among the members of the community by referring to the Quran and teachings of the Prophet, peace be upon him
Keywords: security peace; the Holy Quran; Islamic studies; Islam